Towards a critical reading aesthetic texts: A new textbook for students of aesthetics at the University of Prešov - Slávka Kopčáková (ESPES)
Book review of Makky, L. (2024) Kritické čítanie estetických textov. Autor, text, čitateľ. Prešov: Vydavateľstvo Prešovskej univerzity. 164 s. ISBN 978-80-555-3360-5.